Pengembangan Sistem Informasi Manajemen Sarana Prasarana (Studi Pada: SMK Muhammadiyah 1 Malang) - M. Abdul Algoniu; Satrio Agung Wicaksono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SMK Muhammadiyah 1 Malang is one of the academic institutions that is following the development of information technology in the inventory of infrastructure facilities. In the process of inventorying infrastructure, still applying bookkeeping and assistance from Ms. Excel. This raises a problem, namely the slow information needed to find out the amount of data on facilities and infrastructure in schools. Based on the problems identified, in this study developed a web-based infrastructure infrastructure management information system in the inventory process. This study applies the Waterfall System Development Life Cycle (SDLC) without the deployment process. In analyzing system requirements, this study applies interview methods and observation methods to physical documents on school inventories. From the results of interviews and observations, there were 3 (three) users / actors, namely staff, waka (wakil kepala), and school principals with 17 needs for functionality in the system. From the results of the analysis of needs that have been obtained, then enter the modeling phase applying a unified modeling language. The implementation stages apply the programming language PHP, CodeIgniter framework, and Mysql. In the testing process applying the black-box testing and UAT (user acceptance testing) method. From the black-box testing, the results show that the functionality requirements are 100% valid, while the user acceptance testing (UAT) results are outlined, the application is running well and all functions are running well.